Facies Analysis, Sedimentology and Paleocurrent of The Quaternary Nenering Formation, Pengkalan Hulu, Malaysia - Ulfa, Yuniarti; Yu, Evonne Hooi Rong; Kit, Ooi Cheng (BRIN Publishing, 2014)
Nenering Formation is essentially made up of semi-consolidated sediments, which are divided into basal conglomerate beds, conglomeratic sandstone, cross-bedded sandstone, and siltstone to muddy layers facies. It is overlie unconformable to the Berapit Formation, but conformable to the Kroh and Grik Formations. The stratigraphy of Nenering Formation is a fining upwards sequence where the thickness of conglomerate beds become thinner upwards and become thicker for conglomeratic sandstone. The thickness varies from 0.5 m to tenths of meters. The more sandy in the upper portion (cross-bedded sandstone) overlie with thin siltstone and mudstone facies. The clast and grain composition suggested that the material making up the sedimentary sequence were derived predominantly from the erosion of granitoid rocks and sedimentary and metamorphic rocks constitute a minor provenance. Imbrications and the trend sizes of clasts indicate that the palaeo-current flow toward northeast. Cross bedding that was found in conglomerate and sandstone indicates the main channel depositional environment. The sequence stratigraphy of this area match with the Saskatchewan fluvial braided channel model.